2012
DOI: 10.1177/0954410011434884
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wing span on the aerodynamics of wings in ground effect

Abstract: A computational fluid dynamics study of the influence of wing span has been conducted for an inverted wing with endplates in ground effect. Aerodynamic coefficients were determined for different spans at different ground clearances, highlighting a trend for shorter spans to delay the onset of both separation and resulting loss of negative lift. The vortices at the wing endplates were not observed to change significantly in terms of strength and size; thus, at shorter spans, their influence over a larger percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Due to the requirements of regulations, the wheels are exposed and therefore can contribute up to 40% of the vehicle's total drag (4) . The aerodynamic performance of front wings in isolation has been studied extensively in recent years (5)(6)(7)(8)(9)(10) , and several other reports on isolated.wheels have also increased knowledge about wheel performance when free of wing interference (11)(12)(13)(14)(15) . Intuitively, the close proximity of the front wheels to the front wing would be expected to have a strong influence on the overall system performance, yet the physics associated with the interaction of these two components remains poorly understood (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the requirements of regulations, the wheels are exposed and therefore can contribute up to 40% of the vehicle's total drag (4) . The aerodynamic performance of front wings in isolation has been studied extensively in recent years (5)(6)(7)(8)(9)(10) , and several other reports on isolated.wheels have also increased knowledge about wheel performance when free of wing interference (11)(12)(13)(14)(15) . Intuitively, the close proximity of the front wheels to the front wing would be expected to have a strong influence on the overall system performance, yet the physics associated with the interaction of these two components remains poorly understood (1) .…”
Section: Introductionmentioning
confidence: 99%
“…This remains the only significant full-scale study of its kind in public literature to the best of the authors' knowledge. A moving ground was present in the wind tunnel, and tests were run at 30ms -1 , matching previous front wing work conducted in the same tunnel (6)(7)(8)(9)(10) . A generic double element wing was used with vertical endplates, and the wheels were rigid carbon fibre with a small amount of camber.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of ground-effect research has focused on high Reynolds number flows Re > 10 5 passing over thick and rigid wings (Qu et al, 2014(Qu et al, , 2015 and their application on large Wing-In-Ground (WIG) vehicles (Van Beek and Oskam, 1998;Carter, 1961;Lee et al, 2011), Formula-one aerodynamics (Zhang and Zerihan, 2003;Diasinos et al, 2012), or trains (Moon et al, 2005). A reduction in airfoil thickness is found to benefit (lift producing) wings in groundeffect by reducing drag and lowering the risk of negative down-force caused by the Venturi effect (suction on lower concave surface) (Rad and Kazemi, 2001;Moon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that the down-force increases as the angle of attack increases. Diasinos et al [19] conducted a 3-D CFD study of the influence of wing span for an inverted wing with endplates with ground effect. The airfoil used was modified NASA GA(W) LS (1)-0413.…”
Section: Introductionmentioning
confidence: 99%